2012
DOI: 10.4236/jbbs.2012.24056
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment Discrimination Behavior in Spontaneously Hypertensive Rats

Abstract: Objectives: 1) To reveal, among spontaneously hypertensive rats, subpopulations that diverge in attention to objects enriching an empty cross-maze; 2) To evaluate effect of clinically efficient drug for treatment of attention deficiency atomoxetine on the attention to environmental cues in attentionally-low rats. Method: A novel paradigm that provides measure of attention towards enriching objects independent of general locomotor activity and spatial orientation is employed. The apparatus consists of 4-arm rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
(44 reference statements)
1
3
0
Order By: Relevance
“…The findings of the present study in mice generalize and extend results previously reported in spontaneously hypertensive rats [18]. Both the species include individuals of attentionally-low and -high phenotypes.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The findings of the present study in mice generalize and extend results previously reported in spontaneously hypertensive rats [18]. Both the species include individuals of attentionally-low and -high phenotypes.…”
Section: Discussionsupporting
confidence: 89%
“…The sequence and timing of arms visited were recorded directly into a personal computer by the use of Behavset 3.0 software. The floor and the objects in arms were cleaned thoroughly with paper towel damped in 70% ethanol and were air-dried after each trial [18]. The position of the objects in a pair of opposite arm (#1 and #3, or #2 and #4) was alternated in a quasi-random order.…”
Section: Enrichment Discrimination Testmentioning
confidence: 99%
See 2 more Smart Citations